Return on investment for workplace training: the Canadian experience. (12th February 2013) - Percival, Jennifer C.; Cozzarin, Brian P.; Formaneck, Steven D.
<x xml:space="preserve">Abstract</x> One of the central problems in managing technological change and maintaining a competitive advantage in business is improving the skills of the workforce through investment in human capital and a variety of training practices. This paper explores the evidence on the impact of training investment on productivity in 14 Canadian industries from 1999 to 2005. Our productivity analysis demonstrates that in 12 out of 14 industries, training had a positive effect on productivity. However, when the analysis is put within a financial context, the return on investment was positive in only four industries. Faced with negative rates of return, why should managers in most of the industries in the study promote investment in training? Probably the best explanation is that new technology requires an investment in training. The investment in training is necessary just for the firm to maintain its current labour productivity. Employee turnover necessarily impedes the efficacy of training, because trained workers leave, and untrained workers arrive. Thus, training in this instance again is necessary just to maintain current labour productivity.